A Diffraction Grating Imaging Optimization Method Based on Inverse Operation Algorithm - Qi, Bailin; Zhao, Yuxian; Zhou, Yuzhe (Journal of Theory and Practice of Management Science, 2025)
This article proposes an optimization method for diffraction grating imaging based on inverse operation algorithm. This method addresses the issues of uneven light intensity distribution and image distortion in the imaging process of diffraction gratings. By constructing an inverse operation model, the diffraction effect of the grating is numerically simulated and compensated. Firstly, we conducted a detailed analysis of the physical mechanism and influencing factors of grating diffraction, and then established a forward model for grating diffraction. Subsequently, based on this, we designed an inverse operation algorithm to solve the grating structure parameters in reverse through iterative optimization methods, in order to achieve the goal of optimizing imaging quality. The experimental results show that this optimization method can significantly improve the resolution and contrast of diffraction grating imaging, providing strong support for diffraction gratings applied in high-precision imaging fields and effectively suppressing diffraction fringes and noise in images.